10.1016/s1558-0164(12)70235-3 (CrossRef Listing of Deleted DOIs, 2000)
Introduction Chronic pain and harmful alcohol use are prevalent and disabling conditions with shared neurobiological and social determinants, yet their relationship remains understudied in low- and middle-income countries. Methods Cross-sectional data from 90,846 adults with complete data on the 2019 Brazilian National Health Survey were analysed. Chronic pain was categorised as back pain, rheumatism/arthritis and repetitive strain injury/work-related musculoskeletal disorder. Alcohol use was assessed by consumption frequency (six categories), binge drinking and average daily intake. Weighted logistic regression models adjusted for sociodemographic and clinical variables were applied. Results A U-shaped association was observed between alcohol consumption frequency and chronic pain: compared with regular-high frequency drinkers (3-5 days/week, reference), higher odds of chronic pain were observed among near-daily (odds ratio [OR] 1.73; 95% confidence interval [CI] 1.17-2.56), occasional (OR 1.61; 95% CI 1.20-2.15), infrequent (OR 1.42; 95% CI 1.11-1.82) and regular-low (1-2 days/week; OR 1.28; 95% CI 1.03-1.60) drinkers. Binge drinking was independently associated with higher odds of chronic pain (OR 1.21; 95% CI 1.03-1.42). Female sex (OR 1.65; 95% CI 1.49-1.83) and depression (OR 2.67; CI 2.32-3.07) showed strong associations with chronic pain. Alcohol quantity (g/day) was not significantly associated with chronic pain in sensitivity analyses. Discussion and conclusions Frequent alcohol use, binge drinking, female sex and depression were independently associated with chronic pain in this low- and middle-income countries population. These associations highlight the importance of addressing behavioural and mental health patterns in pain management. Future longitudinal studies are needed to determine the directionality of these associations.